Mitigating error propagation effects in a decision feedback equalizer. - Reuter, M.
We present an approximate analysis approach to the computation of the probability of error and mean burst error length for a decision feedback equalizer (DFE) that takes into account feedback of decision errors. The method uses a reduced-state Markov model of the feedback process and is applicable to linear modulation formats. We use this technique to analyze a DFE design that mitigates the effects of feedback error by incorporating a soft decision device into the feedback path and a norm constraint on the feedback filter weights. We apply the DFE design and analysis approach to a dispersive multipath propagation environment
Keywords: DFE; DFE design; ISI suppression; M-PSK.; M-ary phase shift keying; Approximate analysis; Decision errors feedback; Decision feedback equalizer; Dispersive multipath propagation environment; Error probability; Error propagation effects mitigation; Feedback filter weights; Intersymbol interference; Linear modulation formats; Mean burst error length; Norm constraint; Reduced-state Markov model; Soft decision device